Analisis Keterampilan Manajerial (Teknis, Human, Konseptual) Pemilik UMKM dan Dampaknya terhadap Inovasi Produk - Ismi Zuliyanti; Suwandi (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the managerial skills possessed by Micro, Small and Medium Enterprises (MSMEs) owners, which include technical skills, human skills, and conceptual skills and their influence on product innovation. MSMEs play an important role in supporting the Indonesian economy, but challenges in product innovation are still a major obstacle. The results show that technical and human skills have a significant influence on product innovation, while conceptual skills play an important role in long-term development strategies. The implications of this study underline the importance of integrated managerial training to improve the competitiveness of MSMEs.